Fatigue life prediction of asphalt binders under variable loading levels based on dissipated pseudo-strain energy - Chenze Fang; Hui Li; Zhenxia Li; Yuanzhao Chen; Tengteng Guo (Case Studies in Construction Materials)
Miner’s criterion is popularized to develop the conventional fatigue life prediction model for estimating the service life corresponding to fixed loading level. However, the conventional model makes it difficult to recognize the significant dependency of the fatigue life of viscoelastic asphalt binders on the interaction and sequence produced by variable loading levels. The main objective of this study is to propose a fatigue life prediction method for asphalt binders considering such two factors. First, the loading levels of high stress (σH) and low stress (σL) were applied on asphalt binders for carrying out the fixed loading level fatigue (FLLF) tests. Then, the variable loading level fatigue (VLLF) tests were performed according to the different loading level sequences namely low-high level (σL-σH) and high-low level (σH-σL). Furthermore, the evolution law and increment process of fatigue damage for the tested binders were analyzed using the fatigue damage characterized by dissipated pseudo-strain energy (DPSE). Finally, a binder fatigue life prediction model considering the sequence and interaction of variable loading levels according to damage equivalent criterion. It is shown that the DPSE can accurately characterize the fatigue cracking induced in asphalt binders by separating the viscoelastic dissipated energy that does not contribute to fatigue damage. The DPSE-based binder fatigue damage presents a nonlinear evolution process. The obtained binder fatigue life for the loading level sequences of σH-σL and σL-σH are negatively and positively correlated with the first life ratio, respectively. The binder fatigue life is affected by both the sequence and interaction of variable loading levels. The established prediction model considering such two factors can accurately determine the corresponding fatigue life.